2018
DOI: 10.3390/ijerph15081637
|View full text |Cite
|
Sign up to set email alerts
|

Clients’ Experience and Satisfaction of Utilizing Healthcare Services in a Community Based Health Insurance Program in Bangladesh

Abstract: Background: Community-based health insurance is recognized as a promising tool for health system improvement for low-income people that improves the health status of enrolees and enhances productivity and labor supply. The experience and opinion of the clients who utilized health services through the insurance scheme are important for improving healthcare services, shaping health policies and providing feedback on the quality, availability, and responsiveness of healthcare services. However, studies focusing o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
45
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(61 citation statements)
references
References 50 publications
9
45
5
Order By: Relevance
“…In a study conducted in China, in 14 public hospitals, it is showed that patients' satisfaction level is high (Cronbach's alpha was 0.949) [28]. In another study developed in Bangladesh a high level of satisfaction with health services was found (score 4.17 from 5.0, Cronbach's alpha was 0.93) [57].…”
Section: Discussionmentioning
confidence: 99%
“…In a study conducted in China, in 14 public hospitals, it is showed that patients' satisfaction level is high (Cronbach's alpha was 0.949) [28]. In another study developed in Bangladesh a high level of satisfaction with health services was found (score 4.17 from 5.0, Cronbach's alpha was 0.93) [57].…”
Section: Discussionmentioning
confidence: 99%
“…It routinely monitors and evaluates the hospitals to ensure that NHIS participants in Indonesia have received appropriate services. This was supported by Sarker et al, (2018) research which mentioned the satisfaction with comprehensive services provided by health facilities from patients using the insurance scheme, with a mean of 4.09 ± 0.85 (95% CI: 3.98-4.20) of 5.00.…”
Section: Discussion Of Resultsmentioning
confidence: 76%
“…The most satisfying components were regarding diagnostic services, prescribed drugs explanation, environments around health facilities, and behavior of health workers towards patients. Studies related to patient satisfaction can contribute to the design of the health system with an insurance scheme accompanied by a public health financing strategy to develop health insurance as part of achieving UHC (Sarker et al, 2018). The results of this study indicated that the highest level of patient satisfaction in all elements was from the respondents who paid using NHIS and the lowest was from the respondents who paid with KIS, except for element C Service Time, in which the highest level of satisfaction was from the respondents with his own funding and the smallest was from the respondents with other insurance payments.…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…The purpose of this research is to study the correlations between sustainable tourism, economics, population, and exhibition-driven tourism. Descriptive statistics and a correlation analysis (a one-way ANOVA and a Pearson correlation analysis in SPSS26) were performed on the three hypotheses ( Figure 1) and their panel data [22]. At the same time, the conclusions of this paper provide some positive support and show the impact of Japanese art exhibitions.…”
Section: The Logical Model and Purposementioning
confidence: 67%